Enhanced field-scale characterization for watershed erosion assessments. (July 2019) - Momm, H.G.; Bingner, R.L.; Wells, R.R.; Porter, W.S.; Yasarer, L.; Dabney, S.M.
Abstract: Watershed-scale simulation technology allows quantification of the impact of individual and/or integrated management practices throughout the watershed. In the AnnAGNPS watershed-scale model, the watershed is subdivided into basic modeling units (fields) in which all spatially varying physical parameters are assumed to be homogeneous. Conversely, RUSLE2 model can estimate sediment yield at sub-field scale with enhanced characterization capabilities. In this study, an integrated approach was developed and evaluated that combines both models for enhanced representation of individual fields while accounting for the watershed-wide integrated intra fields effect when routing sediment loads through the watershed. Critical sediment producing areas identified through integrated RUSLE2 erosion and AnnAGNPS sediment transport models can be used to support the development and evaluation of conservation management plans specific to fields but impacting the entire watershed. Highlights: Watershed simulation integrating field-scale descriptions of erosional processes. U.S. Department of Agriculture AnnAGNPS and RUSLE2 integrated technology. Multi-segmented slope profiles improved modeling capability at finer scale. Integrated solution allows evaluation of field practices at watershed scales.